Adaptive radio propagation model for modern road infrastructure units in Vehicular Ad Hoc networks / Muhammad Ahsan Qureshi - Muhammad Ahsan, Qureshi (2016)

(untitled)
Vehicular Ad Hoc Networks (VANETs) is an evolving field of wireless technology having a wide range of useful applications. The deployment and testing of new applications and protocols in VANETs is costly and labor intensive, so the simulation provides a cost effective solution for the evaluation of new applications and protocols. The Radio Propagation Models (RPMs) are employed in VANETs to predict signal attenuation and radio coverage. The RPMs require realistic detail due to restrictively fast mobility of vehicles, nature of network and the underlying road infrastructure units. Modern vehicular environment contains road infrastructure units such as confined curved roads, flyovers, underpasses, straight roads and tunnels. Two types of radio obstacles exist in vehicular environment that impede radio signals; static obstacles (such as buildings), and the moving obstacles (such as large buses). The radio signals in 5.9 GHz band (IEEE 802.11p) are less penetrating as compared to Wi-Fi and GSM which operate in 2.4 GHz and 1.8GHz band respectively. The radio obstacles have high impact on vehicular communication and maintaining the Line-Of-Sight condition among communicating vehicles improves vehicular communication. Hence, developing realistic RPMs in VANETs for the modern road infrastructure units is a challenging task. The existing RPMs do not inspect the impact of modern road infrastructure units on radio propagation in the presence of radio obstacles. Further, no set of rules exists for optimal positioning of Road Side Units (RSUs) on modern road infrastructure units to facilitate reliable communication. Accurate prediction of signal attenuation requires realistic RPM that is capable of addressing physical factors, models both static and moving radio obstacles, considers the modern road infrastructure units and utilize realistic traffic detail found in actual traffic environment. However, incorporation of the required level of detail in an RPM demands extensive computations. Therefore, a light-weight RPM for modern road infrastructure units is needed to predict signal attenuation iv with acceptable accuracy. This research focuses on the development of an adaptive RPM with static and moving obstacle modeling that considers modern road infrastructure units to facilitate pragmatic simulation in VANETs and to provide reliable communication infrastructure. The proposed adaptive RPM selects among different modes of calculating signal attenuation depending upon the existing traffic conditions and underlying road infrastructure units along with the handling of radio obstacles. The adaptive RPM is evaluated on a small scale using real-world data obtained from extensive field measurement campaigns and also on a large scale using simulation. Optimal positioning of RSUs on modern road infrastructure units to maintain LOS condition among communicating vehicles is formulized using geometric concepts. Finally, a comparison is made between the two cases (presence and absence of RSUs at optimal distance) in terms of system evaluation metrics. This research redirects the existing efforts in the design of propagation models towards a novel perception by which to incorporate adaptability in propagation models as a benchmark towards realistic performance evaluation of new advancements.